The Construction of Media Reality on Judicial Mafia News (Critical Discourse Analysis Study of Bibit and Chandra Case on Bang One Show) - Aden Hidayat (KOM & REALITAS SOSIAL, 2010)
Purpose of the research is divided into four, which are, the curiosity on discourse that is done by Bang One Show in judicial mafia presentation, the editorial reason for choosing judicial mafia, editorial concern or market condition, considered social-culture factors. This research is using the criticism of paradigm with critical discourse analysis qualitative approach. This critical discourse analysis adopts Fairclough model. This model emphasizes on four levels, those are; text, production, consumption, and social-culture. On text level, the result of this research of Bang One Show's presentation in expressing judicial mafia, shows advocacy to Bibit and Chandra and boxes Anggodo into a corner. This becomes editorial's political attitude to take sides to Bibit and Chandra. Editorial selection on production level about judicial mafia discourse of Bibit and Chandra case, can not be separated from economical interest that is seen both from market and social interests. However, unfortunately, on production level, the social interest is inconsistently done forever, which is proved, there is not even a single program relates to the stockholder news that is assumed it has damaged public interest. On the discourse level of consumption that wins Bibit and Chandra, the editorial staff has concerned with public attention. Social-culture, as the last level in Bang One Show, concerns the social condition at that time, as judicial mafia of Bibit and Chandra case was on aired, the public opinion tended to Bibit and Chandra advocacy, and cross examination on Anggodo. From the four levels, it can be concluded that the reality or meaningful discourse, is certainly influenced by internal factors and media external.